Influence of EMG signal determination on the reliability of some EMG parameters often used for the evaluation of explosive force production - Trost Bobic, T.; Sarabon, N.; Markovic, G. (17th Annual Congress of the European College of Sport Science (ECSS), Bruges, 4. -7. July 2012, 2012)
The aim of this study was to asses if the method used for EMG signal onset determination would affect inter- and intra-session reliability of multiple electromyographic (EMG) indexes often used to asses explosive force production of m. soleus (EFPS). Methods: Thirty-seven physical education students (22.5±1.3 years) where included in the intra-session, while ten (22.7±0.9 years) where included in the inter-session reliability study. Sitting on a custom made dynamometer, participants were asked to perform three unilateral maximal volontary isometric plantar flexions (MVIC) of the right foot stressing explosive force production. EMG signals of m. soleus where recorded by means of surface bipolar electrodes. In order to test if the method used for EMG signal onset determination would affect inter- and intra-session reliability of EFPS indexes, firstly, the Hodges and Bui method for EMG signal onset determination was used, and inter- and intra-session reliability was calculated for 27 EFPS indexes. The same procedure was repeated with the four most reliable indexes, setting onset of EMG signal: 1) at 3% MVIC, 2) at 3% MVC - 5ms, and 3) at 3% MVIC - 70 ms (Aagaard et al., 2002).Three components of reliability were calcuated: systematic bias, within-individual variation, and retest correlation (Hopkins, 2000). Results: Intra-session reliability - The within-individual variation (expressed as CV), did not differ drammatically between different onset methods for MVIC normalized root mean square (R), average EMG value (A) and time integral (I) calculated in the time interval of 200ms. The within-individual variation of the rate of EMG rise (RER), calculated in the time interval of 75ms resulted significantly lower when the onset was set on 3%MVC - 70ms (27.59 %, CI: 23.45 - 33.54 %), than when it was set on 3% MVC (117.33 %, 99.70 - 142.59 %). ICC values followed the same trend. Inter-session reliability - Again, only the within-individual variation of the RER0-75 index resulted significantly lower when the onset was set on 3%MVC - 70ms (39.71 %, CI: 28.47 - 65.55 %), than when it was set on 3% MVC (151.38 %, 108.55 - 249.89 %), indicating greater inter-session reliability when the first method is used. Discussion: Contrary to previous findings (Hodges & Bui, 1996), the method of EMG onset determination did not influenced the reliability of all the indexes tested. On the other hand, it influenced noticeably the reliability of the RER0-75 index.